Distributed Encoding and Decoding of Quantum Information over Networks. Issue 1 (18th December 2018) - Yamasaki, Hayata; Murao, Mio
Abstract: Encoding and decoding quantum information in a multipartite quantum system are indispensable for quantum error correction and also play crucial roles in multiparty tasks in distributed quantum information processing such as quantum secret sharing. To quantitatively characterize nonlocal properties of multipartite quantum transformations for encoding and decoding, we analyze the entanglement costs of encoding and decoding quantum information in a multipartite quantum system distributed among spatially separated parties connected by a network. This analysis generalizes previous studies of entanglement costs for preparing bipartite and multipartite quantum states and implementing bipartite quantum transformations by entanglement‐assisted local operations and classical communication (LOCC). We identify conditions for the parties being able to encode or decode quantum information in the distributed quantum system deterministically and exactly, when inter‐party quantum communication is restricted to a tree‐topology network. In our analysis, we reduce the multiparty tasks of implementing the encoding and decoding to sequential applications of one‐shot zero‐error quantum state splitting and merging for two parties. While encoding and decoding are inverse tasks of each other, our results suggest that a quantitative difference in entanglement cost between encoding and decoding arises due to the difference between quantum state merging and splitting. Abstract : Costs of implementing multipartite nonlocal quantum state transformations for encoding and decoding quantum information are analyzed, progressing beyond entanglement costs defined for bipartite and multipartite quantum states and bipartite transformations. Difference between encoding and decoding is quantitatively characterized in terms of their implementation costs in distributed quantum information processing on a given tree‐topology network for quantum communication.